Water Mass Characteristic in The Eastern Inflow Region of The Indonesian Throughflow During Leg-3 of Nusa Manggala Expedition (December 2018). Issue 1 (December 2020) - Putri, M R; Anwar, I P; Avrionesti,; Surinati, D
Abstract: The Nusa Manggala (ENM) leg-3 expedition in 2018 was held on December 6-16 2018. The survey achieved eighteen Conductivity Temperature Depth measurement points and centered at North of West Papua and Halmahera Sea as the inflow area of eastern part of Indonesian Throughflow (ITF). The results of this study prove that Pacific Surface Water is present on the surface up to 70 m with a temperature of 26 °C - 30°C and salinity of 24 psu – 24.5 psu. Then, South Pacific Subtropical Water and South Pacific Intermediate Water are simultaneously 70 m - 250 m and 250 m - 1000 m at the northern of Halmahera Sea. They not exceed till the southern part of Halmahera Sea.